Art, Ecopedagogy and Digital Media for Environmental Awareness in Elementary Schools: A Narrative Review - Niswatun Khalim; Nurul Istiq’faroh; Suryanti Suryanti (Universitas Negeri Padang, 2026)
This narrative literature review examines environmental education in elementary schools, with a particular focus on making learning more contextual, engaging, and connected to students' lived experiences. Climate change is often perceived as an abstract phenomenon, rendering conceptual explanations alone insufficient for fostering meaningful understanding among young learners. This review synthesizes 15 literature sources, comprising 12 empirical studies (including research and development, pre-experimental, classroom action research, and mixed-methods studies), 2 conceptual articles, and 1 global policy report, published between 2017 and 2025. The sources address teaching materials, digital media, ecopedagogy, ecoliteracy, STEAM-PjBL, and arts-based environmental education. Literature selection was conducted through purposive sampling with clearly defined inclusion and exclusion criteria, followed by thematic analysis to identify convergent patterns, divergent findings, and research gaps across the corpus. The findings indicate that supplementary teaching materials, interactive e-modules, game-based E-LKPD, and digital media enhance student engagement by presenting content visually, interactively, and in alignment with elementary learners' developmental characteristics. Ecopedagogical and ecoliteracy approaches further support students in understanding environmental issues, cultivating concern, and translating awareness into tangible actions. Art integration provides expressive and affective entry points, enabling students to engage emotionally with environmental challenges and develop deeper comprehension of climate change. The main contribution of this review is a triadic conceptual framework that integrates art, ecopedagogy, and innovative digital media to foster environmental awareness among elementary school students, a synthesis that addresses a gap in existing literature where these three dimensions have largely been examined in isolation.